BLEEDING HEART - Rini Istiyani; Ruth Ambarsari; Salim (Canthing, 2022)
Fashion design in this Final Project aims to create a party fashion design that combines the source of ideas and fashion styles that have been selected. The source of ideas from this design is Bleeding Heart. Bleeding Heart itself is incorporated into clothing with the application of the Pattern Magic pattern and the Water Marble technique as a fashion motif, while the fashion style is the glamor style. The type of clothing chosen was evening party clothing. The materials used in this design are satin bridal and organza materials for water marble. The colors of the materials in this design follow the color of the source of the idea. In this final project design clothes are made specifically for women on the occasion of night parties with ages 21 to 26 years. This Final Project is made in standard size, that is m2. And usually used by upper adult women. Keywords: Bleeding Heart style glamour